Feasibility and pilot study of passive heat therapy on cardiovascular performance and laboratory values in older adults - Flynn, Brigid; Vitztum, Michelle; Miller, Joshua; Houchin, Abigail; Kim, Jaromme; He, Jianghua; Geiger, Paige (Pilot and feasibility studies, 2023)
Background Chronic heat therapy may have beneficial effects on cardiovascular function. These effects may be more pronounced in older adults. We performed a pilot feasibility study of repeated heat therapy sessions in a hot tub (40.5 °C) in older adults while wearing a noninvasive hemodynamic monitor. As part of the protocol, the volunteers underwent cardiovascular performance testing pre- and post-intervention. Methods Fifteen volunteers > 50 years old underwent 8–10 separate 45-min hot tub session over 14 days in this exploratory and mixed methods trial. The participants had maximal oxygen consumption (VO 2 max) and other cardiovascular data measured via exercise treadmill testing prior to and after all hot tub sessions. The participants also wore noninvasive fingertip volume clamp monitors while immerged in hot water that calculated systemic vascular resistance, heart rate, blood pressure, and cardiac output in order to ascertain the feasibility and utility of this data. Other laboratory studies were obtained pre- and post-intervention. The protocol was determined feasible if the heat therapy and cardiovascular testing was completed by at least 90% (14/15 subjects). Feasibility of the noninvasive monitor was determined by the fidelity of the results. Secondary exploratory outcomes were analyzed for differences to identify if they are acceptable to include in an efficacy trial. Results All participants completed the study protocol identifying the feasibility of the protocol. The noninvasive hemodynamic monitors successfully recorded cardiac output, systemic vascular resistance, heart rate, and blood pressure with fidelity based on the analysis of recordings. In the secondary analyses, we found no difference in the pre- to post-intervention measurement of VO 2 max but did find increased exercise duration following hot tub therapy compared with prior to the therapy (571 s versus 551 s). Conclusions The current pilot study protocol is feasible for the purpose of analyzing the effects of heat therapy and cardiovascular performance in older adults while wearing a noninvasive hemodynamic monitor and undergoing treadmill stress testing. Secondary analyses found increased exercise tolerance but no differences in VO 2 max following heat sessions.